Adaptação transcultural e propriedades de medida da versão em português brasileiro do pain stages of change questionnaire em pacientes com dor lombar crônica inespecífica - Pereira, Roger Berg (2025)
Introduction: Readiness for change as an individual variable denotes a useful strategy to understand how to customize interventions to promote adherence or even identify which aspects/barriers impact engagement with the new behavior, such as exercise practice, one of the desirable behavior changes in the management of nonspecific chronic low back pain (CLBP), in addition to contributing to greater long-term treatment effectiveness. The Pain Stages of Change Questionnaire (PSOCQ) is a measure of patient readiness for pain self-management that has proven acceptable in other countries. However, there is still no Brazilian version of the PSOCQ (PSOCQ-Br). Objective: To perform a cross-cultural adaptation and verify the measurement properties of the Brazilian version of the PSOCQ. Design: Measurement property study. Methods: The cross-cultural adaptation was conducted according to the recommended guidelines. The PSOCQ-Br was administered to 150 participants with nonspecific CLBP. Confirmatory factor analysis with the following fit indices: Chi-Square (CMIN), the ratio of CMIN divided by degrees of freedom (DF) (CMIN/DF), Root Mean Square Error of Approximation (RMSEA), Comparative Fit Index (CFI), and Tucker Lewis Index (TLI), and Pearson's correlation were used to assess construct validity. The intraclass correlation coefficient (ICC) and Cronbach's α were used to assess test-retest reliability and internal consistency, respectively, in addition to the analysis of the Standard Error of Measurement (SEM) and the Smallest Detectable Change (SDC). Results: The adapted version maintained its equivalence and applicability in the Brazilian context. The PSOCQ-Br demonstrated acceptable indices of structural validity through confirmatory factor analysis for a model with 4 subscales. Cronbach's α for each PSOCQ-Br subscale was above 0.70. The ICC for each subscale was also above 0.70 (95%CI 0.72–0.85). The SDC for Precontemplation, Contemplation, Action, and Maintenance were, respectively, 0.97, 1.08, 1.03, and 1.05. The construct validity hypotheses were confirmed for the contemplation (83%), action (94%), and maintenance (83%) subscales, except for the precontemplation subscale, in which only 72% of the hypotheses were confirmed. Conclusion: The PSOCQ-Br demonstrated adequate measurement properties that were comparable to the original English version and other languages. Therefore, it can be recommended for use in clinical practice and research to assess readiness for change in individuals with CLBP.